Environmental risk factors in paediatric inflammatory bowel diseases: a population based case control study. Issue 3 (11th February 2005) - Baron, S; Turck, D; Leplat, C; Merle, V; Gower-Rousseau, C; Marti, R; Yzet, T; Lerebours, E; Dupas, J-L; Debeugny, S; Salomez, J-L; Cortot, A; et al.
Abstract : Background: Environmental exposures in early life have been implicated in the aetiology of inflammatory bowel disease. Objective: To examine environmental risk factors prior to the development of inflammatory bowel disease in a paediatric population based case control study. Methods: A total of 222 incident cases of Crohn's disease and 60 incident cases of ulcerative colitis occurring before 17 years of age between January 1988 and December 1997 were matched with one control subject by sex, age, and geographical location. We recorded 140 study variables in a questionnaire that covered familial history of inflammatory bowel disease, events during the perinatal period, infant and child diet, vaccinations and childhood diseases, household amenities, and the family's socioeconomic status. Results: In a multivariate model, familial history of inflammatory bowel disease (odds ratio (OR) 4.3 (95% confidence interval 2.3–8)), breast feeding (OR 2.1 (1.3–3.4)), bacille Calmette-Guerin vaccination (OR 3.6 (1.1–11.9)), and history of eczema (OR 2.1 (1–4.5)) were significant risk factors for Crohn's disease whereas regular drinking of tap water was a protective factor (OR 0.56 (0.3–1)). Familial history of inflammatory bowel disease (OR 12.5 (2.2–71.4)), disease during pregnancy (OR 8.9 (1.5–52)), and bedroom sharing (OR 7.1 (1.9–27.4)) were risk factors for ulcerative colitis whereas appendicectomy was a protective factor (OR 0.06 (0.01–0.36)). Conclusions: While family history and appendicectomy are known risk factors, changes in risk based on domestic promiscuity, certain vaccinations, and dietary factors may provide new aetiological clues.